Sea Level Rise in Indonesia: The Drivers and the Combined Impacts from Land Subsidence - Karlina Triana; A'an Johan Wahyudi (ASEAN Journal on Science and Technology for Development, 2020)
Sea level changes play an important role as an indicator of climate change. However, without climate change, the sea level itself shows strong regional patterns, both in space and time, that could deviate significantly from global averages. The spatial variability of sea level changes in Indonesia can be divided based on its drivers, i.e., climatic and seasonal weather-driven and non-climatic and geological-driven. Seasonally, the sea level in Indonesia is generally high in northwest monsoon and low in southeast monsoon. Nevertheless, there is a possibility of extreme natural phenomenon influences that generate anomalies and a thermosteric process that also affects the sea level. On the non-climatic and geological theory, the uniqueness of the tectonic setting in Indonesia will create spatial variations in regional sea levels, as both static and dynamic changes in a long period of time. Land subsidence is also often regarded as a significant contributor to the rise of relative sea level in coastal environments. Combined with the rise in sea level, land subsidence will escalate coastal flooding risks, contribute to shoreline retreat, and be further aggravated by anthropogenic forces such as groundwater extraction and land development. This scientific review will summarize the spatial variation of sea level rise in Indonesia, examines the underlying drivers that control it, and provides an overview of the combined sea level rise and land subsidence as a significant threat in Indonesia.